(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Background The foundation of the healthcare system is primary health care (PHC). Thesignificance of PHC has been acknowledged on a global scale, and policymakers work to enhance PHCsystems. Developing health services is mostly dependent on research in the field. Research in thehealthcare industry helps to recognize and gauge health issues as well as assess the effectiveness ofsolutions used to address a range of health concerns. Objectives This study objective analyse Saudiprimary health care (PHC) research and determined its distribution by topic, period, region, andinstitution. Methods We used PubMed Google Scholar to search the academic literature for ourdescriptive investigation. Relevant journal articles were located by using the MeSH phrases PrimaryHealth Or Saudi Primary Care Or Saudi. Relevant data from journal papers published up untilDecember 2020 was entered into a coding tool. Results There was a total of 548 research papers on PHCresearch published between 1995 - 2020. There was a rising trend in the number of publicationsthroughout time. The majority of publications were primary research papers (88.7), while the vastmajority of studies used a cross-sectional design (93). Topics such as health services research chronic diseases were heavily discussed. The majority of studies were conducted in Riyadh province(48.1) and were published mostly by universities (56.0) Saudi Ministry of Health (24.8).Conclusion Although Saudi Arabia has a robust PHC infrastructure, the country’s research outputs areinadequate. The majority of published publications are university-based cross-sectional studies. Therewill be more evidence for PHC and it will be more easily translated into service delivery if the researchenvironment is improved.